Prevalence and determinants of standard motorcycle crash helmet use among rural postal delivery riders in Peninsular Malaysia - Yellappan, Kaviyarasu (2011)
Motorcycle is the preferred mode of transport in developing countries and the most common vehicle involved in road crashes and fatalities. Head and neck injuries were leading cause of fatality among motorcyclists. Helmets were invented as a mechanism to prevent head injuries. Motorcycle was popular for commercial and leisure activities. Occupational motorcycle riders are known for using motorcycles regularly to work, during work and back from work. Based on records and literature, the history of involvement in crashes among occupational riders has not been recorded properly in Malaysia. Postal delivery riders (PDR) were seen as a vulnerable group compared they were exposed longer hours on the road than average of 2 hours daily during their delivery jobs. This study was designed to identify the determinants that influence the use of standard motorcycle crash helmets among rural postal delivery riders and determine the prevalence of used helmet that complied with helmet standard MS1:1996. A cross sectional study was done among 269 PDR from 50 postal distribution centers throughout Peninsular Malaysia. Observation, interview and mechanical testing method was used during data collection. Standards of motorcycle crash helmet were determined by presence of certification label issued by Standards and Industrial Research Institute of Malaysia (SIRIM) and by SIRIM helmet testing procedures. Descriptive, chi-square and bivariate logistic regression analyses were carried out using PASW Statistics version 18. Prevalence of standard motorcycle crash helmet (by presence of SIRIM label) usage among postal delivery riders (PDR) were 76.6% with response rate of 99.3%. Analysis with presence of SIRIM label as a dependent variable resulted in odds of full shell motorcycle crash helmets having SIRIM label were 37.1 times than half shell helmets. Odds of non-purchased motorcycle crash helmets having SIRIM label were 14.9 times than purchased helmets. The odds of expensive motorcycle crash helmets to have SIRIM sticker were 4.4 times than cheaper motorcycle crash helmets. Motorcycle crash helmets owned by riders without previous crash history had 1.9 odds of having the SIRIM sticker than helmets owned by riders with crash history. Prevalence of standard motorcycle crash helmet (by SIRIM testing results) usage among postal delivery riders (PDR) were 40% with response rate of 61%. In second analysis, SIRIM testing results was used as a dependent variable. The analysis revealed odds of non-purchased helmets to pass the SIRIM testing were 3.7 times the odds of purchased helmets that passed the test. Odds of motorcycle crash helmets with presence of SIRIM label to pass the SIRIM testing were 24.2 times the odds of standard motorcycle crash helmet without the presence of SIRIM label. Odds of standard motorcycle crash helmet used (less than 2 years) to pass the SIRIM testing were 2.5 times the odds of the motorcycle crash helmet used (more than 2 years). Arriving at the conclusion, employers should provide motorcycle crash helmets to the employees. Each helmet provided should be full shell motorcycle crash helmet with the presence of SIRIM label which indicates the helmet is a standard approved helmet. Helmets provided by employer should be purchased by the employer at a price of RM 35.00 or more. Respondents with prior crash history must be monitored closely on the helmet use pattern as they were less likely to wear standard helmets. Helmets used should be replaced once every two years to provide comfort and safety to the employees. As from PDR viewpoint, PDR should be educated and provided with knowledge of standard motorcycle crash helmet. PDR using the helmets provided by the employer were more safe than using own helmets. In the event, PDR not getting helmets provided by the employer, helmets purchased must have SIRIM certification sticker cost not less than RM 35.00 and should be replaced with new helmets every two years.